Advanced technologies management for retailing : frameworks and cases - Pantano, Eleonora, 1982-; Timmermans, H. J. P. (Hershey PA : Business Science Reference, 2011)
'This book contributes to our understanding of applications of new technologies and their impact on the design and development of point of sale systems and on consumers' behavior'--Provided by publisher.
Includes bibliographical references (p. 328-374) and index.
Keywords: Retail trade -- Technological innovations; Retail trade -- Management; Retail trade -- Automation -- Social aspects